Efeitos de dois diferentes protocolos de natação sobre o metabolismo glicêmico, lipídico e equilíbrio redox em camundongos C57BL/6 - Silva, Carlos Eduardo Menezes da (2016)
The aerobic exercise is a powerful tool to combat oxidative stress. Several studies have shown that regular exercise produces antioxidant effects and appears to reduce the incidence of diseases associated with redox imbalance.That way, our aim was to investigate effects of swimming training on oxidative stress and metabolic parameters. Twenty male C57Bl/6 mice (12-16 weeks old), were randomly divided into four groups: two sedentary control (CT4 and CT8; n=4 per group) and two swimming groups (T4 and T8; n=6 per group). Group T4 swam 90 minutes/session, 2 times per day, 5 days/week for 4 weeks. Group T8 swam 90 minutes/session, 1 times per day, 5 days/week for 8 weeks. The animals were sacrificed for analysis of metabolic and antioxidant status Data are expressed as mean±SEM. ANOVA one way was used for statistical analysis. Swimming for 8 weeks was able to decrease significantly the body weight compare to sedentary group, the opposite was observed in the group trained for 4-week. Interestingly, we observed a significant increase in brown adipose tissue in animals of both protocols swimming compared to their respective control groups. On the other hand the plasma lipid profile showed that the levels of cholesterol and nonesterified fatty acid did not differ between the groups. However, plasma triglycerides and VLDL levels were significantly decreased after 4 weeks of swimming, contrary to the 8-week groups did not differ in levels of triglycerides and VLDL. In addition, both protocols decreased the plasma lipid peroxidation. In T4 group, insulin resistance índex was significantly lower than, suggesting improvement in glycemic profile. At the liver, lipid peroxidation did not differ between the groups, but catalase activity was significantly increased in T8 compare to CT8. In gastrocnemius muscle, the activity of catalase and arginase and nitrite levels did not differ between groups. However, lipid peroxidation and superoxide dismutase activity decreased significantly after 8 weeks of swimming protocol In conclusion, the results showed that the duration and frequency of physical exercise modulates unlike antioxidant activity and lipid and glycemic metabolism.